A CONTRASIVE ANALYSIS OF SURFACE STRUCTURE IN BASIC SENTENCE BETWEEN JAVANESE AND MADURESE - Devie Reztia Anjarani; Muhammad Darrin Zuhri; Zainuddin Zainuddin (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: Indonesia has hundreds of local languages, and Javanese and Madurese are parts of them. Jawa and Madura places where those two languages are belong to, are close. This is the reason those two languages influenced each other. These two languages have similar level of language in case of politeness. This study was aimed to answer the following question what the similarities and differences of surface structure in basic sentence between Javanese and Madurese are. This study was conducted in form of qualitative approaches, documents analysis. The data of this study is basic sentences which found in data source, and it must be comparable each other. The result of this study were Madurese and Javanese have similarities in their sentences pattern, while the differences could be found on In forming a question Javanese can be preceded by predicate but it is ended by word “a”. Whereas in Madurese, there is no any ending words to show that a sentence is an interrogative sentence. Keywords: contrastive analysis, surface structure, Javanese and Madurese